A quick screening approach for design of multi-principal element alloy with solid solution phase. (5th October 2019) - Zheng, Mingjie; Ding, Wenyi; Cao, Weitao; Hu, Shenyang; Huang, Qunying
Abstract: Multi-principal element alloys (MPEAs) have wide promising applications. However, the composition design of MPEAs is challenging due to their vast options and complexity. To narrow down the composition options for MPEAs, a quick screening approach based on a two-parameter method was proposed for the MPEA design. Two thermodynamic parameters of the entropy-enthalpy difference ζ and the entropy-enthalpy quotient Ω mod were defined based on a new enthalpy parameter which was proposed as the summation of the weighted enthalpy modulus |Δ H |sum . The phase selection rules for solid solution MPEAs were statistically summarized from 200 experimental data. The two-parameter method based on these two parameters and phase selection rules can well classify the conventional steels, high-entropy steels, high-entropy alloys and amorphous alloys. The quick screening approach developed through the two-parameter method together with Monte Carlo sampling method was applied to the alloy systems of (CoCrFeMnNi)random, Fe50 (CoCrMnNi)random and Fe50 (CoCrMn)random to predict the optimal compositions with stable solid solution phases from millions of options. The theoretical prediction was validated by experimental results. This quick screening approach is applicable to different kinds of MPEAs and can facilitate the research and development of MPEAs as well as other alloys with stable solid solution phases. Graphical abstract: Unlabelled Image Highlights: New thermodynamic parameters and phase selection rules were proposed and verified by various alloys. A two-parameter method proposed for phase selection of MPEAs can well classify various alloys. New CoCrFeMnNi based alloys with solid solution phases were designed and verified through experimental results.